2020
DOI: 10.1002/ctm2.46
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of HSPA6 in Actinidia chinensis Planch. root extract (acRoots)‐inhibited lung cancer proliferation

Abstract: Actinidia chinensis Planch. root extract (acRoots) as one of Chinese traditional medications has been applied for antitumor therapy for decades, although the exact mechanisms have not been revealed. Our present study aimed to define the inhibitory specificity and pattern of acRoots in the lung cancer cell lines by comparing 40 types of cancer cell lines, select acRoots‐associated inflammation target genes from transcriptional profiles of acRoots‐sensitive and less‐sensitive lung cancer cell lines, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
4
17
0
Order By: Relevance
“…HSPA6 and HSPA7 were reported to share more than ninety percent nucleotide identity through their coding regions; but HSPA7 showed no protein-coding potential (11). Although HSPA6 was discovered three decades ago, the functional roles in cancer progression are unclear (12)(13)(14). Recently, HSPA6 was discovered to be dispensable for Withaferin A-mediated apoptosis/autophagy or migration inhibition of breast cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…HSPA6 and HSPA7 were reported to share more than ninety percent nucleotide identity through their coding regions; but HSPA7 showed no protein-coding potential (11). Although HSPA6 was discovered three decades ago, the functional roles in cancer progression are unclear (12)(13)(14). Recently, HSPA6 was discovered to be dispensable for Withaferin A-mediated apoptosis/autophagy or migration inhibition of breast cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Down regulation of HSPA5 can promot ANXA1 and repress PSAT1 expression, whicn inhibiting the osteosarcoma cell proliferation and inducing cell apoptosis [23] . The expression of HSPA6 were found assoicated with the lung cancer [24], leukemia [12] and baldder cancer's [25] migration, invasion and proliferation. HSPA8 could regulate the cell viability in pancreatic cancer cells [26] and serve as a molecular target in human hepatocellular carcinoma [27].…”
Section: Discussionmentioning
confidence: 99%
“…And Pseudogene expression were treated as a novel marker and used in a variety of cancer types to stratify patients subtypes [5] and is therefore should taken into account in cancer survival prognostic factors.The HSPA7 (HSP70B) gene discovered in 1985 and encoded near the highly homologous HSPA6 (HSP70B') on chromosome 1, although mRNA can be expressed after thermal stimulation, it cannot transcribe a functional protein [6]. Numerous investigations have shown that HSPA6 plays an important role in multiple human cancers, including esophageal cancer [7,8], glioma [9], lung cancer [10], hepatocellular carcinoma [11] and leukemia [12].However, little has been reported about the expression and role of HSPA7 in cancer. Our study showed that high expression of HSPA7 can indicate the poor prognosis of KIRC.…”
Section: Introductionmentioning
confidence: 99%
“…The Pseudogene HSPA7 (HSP70B) belongs to the HSP70 family (HSPA), discovered in 1985 and encoded near the highly homologous HSPA6 (HSP70B′) on chromosome 1, although mRNA can be expressed after thermal stimulation, it cannot transcribe a functional protein [ 10 ]. Numerous investigations have shown that HSPA6 plays an important role in multiple human cancers, including esophageal cancer [ 11 , 12 ], glioma [ 13 ], lung cancer [ 14 ], hepatocellular carcinoma [ 15 ] and leukemia [ 16 ]. However, little has been reported about the expression and role of HSPA7 in cancer.…”
Section: Introductionmentioning
confidence: 99%